Investigating Factors Affecting the Prices of Texas Wine Grapes - Murova, Olga I.; Boonsaeng, Tullaya; Williams, Kirk (Archives of Business Research, 2025)
This paper examines the factors affecting wine grape prices in Texas. It also investigates price differentials of grapes based on the type of wine produced – red, white, dry, or sweet. Surveys from the National Agricultural Statistical Surveys for five grape-producing regions of Texas in 2015, 2017, 2019, and 2020 are utilized. Findings reveal that increased grape production and the increased yields in the state lead to decreasing grape prices. Low temperatures result in reduced yields and, consequently, an increase in the prices of white and red grapes. High summer temperatures drive up the prices of white grapes, but not those of red grapes. Models with fixed time effects show that producers received higher grape prices in 2017 and 2020. Drought was the reason for lower grape prices in 2019. An interesting result indicates that grapes used in white wine production, regardless of whether they are dry or sweet, contribute to higher prices received by producers compared to red grapes.